Lessons from human mutations in PPARgamma - Hegele, R A (International journal of obesity (2005), 2005)
Familial partial lipodystrophy (FPLD) is characterized by adipose tissue repartitioning with multiple metabolic disturbances, including insulin resistance and dyslipidemia. Classical FPLD results from mutations in LMNA encoding nuclear lamin A/C (FPLD2), but recently some families with partial lipodystrophy and normal LMNA sequence were found to have germline mutations in PPARgamma (FPLD3). For instance, all four affected subjects in a three-generation Canadian FPLD3 kindred ascertained based upon a clinical diagnosis of partial lipodystrophy were heterozygous for the PPARgamma F388L mutation, which altered a highly conserved residue within helix 8 of the predicted ligand-binding pocket of PPARgamma. The mutation was absent from normal subjects, and functional studies showed that the mutant receptor had significantly decreased basal transcriptional activity and impaired stimulation by rosiglitazone, with no evidence of a dominant-negative mechanism. Other reported FPLD3 patients with mutant PPARgamma were ascertained either directly based on a clinical diagnosis of lipodystrophy (R425C mutation), or based on insulin resistance with subsequent demonstration of lipodystrophy (V290M and P467L mutations). Compared to subjects with mutant LMNA, lipodystrophic subjects with mutant PPARgamma had less severe adipose involvement, together with more severe clinical and biochemical manifestations of insulin resistance, and more variable response to treatment with thiazolidinediones. Thus, rare natural mutations affecting PPARgamma ligand binding and/or transactivation functions cause partial lipodystrophy, with associated components that resemble the metabolic syndrome.